U-Prove extensions - Paquin, Christian (Microsoft Research, 2014)
The U-Prove Cryptographic Specification focuses on the core U-Prove capabilities; the specified features were selected to simplify implementation and integration into existing systems, while meeting the needs of a wide array of scenarios. By design, the specification provides extension points, making it possible to extend the core capabilities to meet additional needs. This paper describes recently released features compatible with the U-Prove technology. The reader is assumed to be familiar with the technology, and is referred to the technology overview for an introduction.